Pengaruh Disiplin Kerja, Kepuasan Kerja Dan Komunikasi Terhadap Kinerja Karyawan Pada PT Putra Jaya Propita - Nabila Husna; Rosinta Romauli Situmeang; Athaya Agnezka; Megawati Sagala (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The background of the research in this study was to examine the effect of work discipline, job satisfaction and communication on employee performance at PT Putra Jaya Propita. Decreased employee performance becomes the basis for researchers to develop factors that cause decreased performance. The objects in this study were employees of PT Putra Jaya Propita with a total population of 76 employees. The research sample was 76 employees using saturated sampling techniques. Research limits theory to the use of theories related to human resource management. The method in this study uses quantitative methods with a causal study research model. The implementation of this research can be a consideration to pay attention to discipline, satisfaction and communication that occurs in the company and its impact on employee performance. The conclusions on the research results indicate that the study accepts the hypothesis that work discipline, job satisfaction and communication have an effect on employee performance at PT Putra Jaya Propita either simultaneously or partially with a determination value of 40.7%.. Keywords : Work Discipline. Job Satisfaction, Communication and Employee Performance